Raising Philadelphia the making of America's first great city, 1750-1775 - McHenry, Justin (Brookline Books, 2024)
"The generation of Philadelphians prior to the American Revolution propelled the meteoric rise of the city into the thriving cultural heart of Colonial America. This is the dramatic story of Philadelphia's ascension over the course of the final decades of colonial America, detailing along the way the lives of the people molding the city in their image. You will travel into the heady salon of Elizabeth Graeme. Be there with David Rittenhouse in his observatory tracking the transit of Venus. Experience the rise and fall of the friendship of John Morgan and William Shippen. Follow Anthony Benezet's crusade against slavery. And witness the transformation of Philadelphia as its citizens gain their political voices to declare their independence. Raising Philadelphia takes the reader through this critical moment in American history to bring to life the vibrancy of Philadelphia as it rose up to become America's first great city"--
Keywords: Geschichte 1750-1775; Philadelphia, Pa.; Philadelphia (Pa.) / History / 18th century